State Defense Education: The Urgence of Challenges and Opportunities in the Society 5.0 Era - Arifin, Arifin (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Globalization is an opportunity and a challenge that must be faced by all citizens of the world, including Indonesia. The development of increasingly advanced information and communication technology will have a positive or negative impact on the sovereignty of a nation. In addition, globalization also provides access to information that is easier and faster to spread throughout the country, creating global transparency where the physical boundaries of a country's sovereignty are threatened with various disturbances and obstacles. This study uses a normative juridical approach aimed at knowing more about state defense education and its urgency in the era of society 5.0, so in order to maintain the integrity and sovereignty of the Indonesian state from various bad things caused by the development of globalization.